DETERMINATION OF AGE FROM SKELETAL STRUCTURES OF POMADASYS HASTA (BLOCH) - Nammalwar, p (Indian Journal of Fisheries, 2011)
Some skeletal stuctures like vertebrae, palatine, cleithrum and operculumappear to be useful in the determination of age of P. hasta. These parts havebeen found useful in determining age of fish by Hart (1950) Menon (1950)Pantulu (1961) and others. Le cren (1947) and Gosline (1960) studied thegrowth rings on bones for determining the age and growth rate of percoid fishes